JAKABARING WATER SPORT CENTER SEBAGAI KAWASAN REKREASI DAN OLAHRAGA AIR YANG NYAMAN DAN BERNUANSA MODERN - Angkasa, Zuber (JURNAL MEDIA TEKNIK, 2011)
ABSTRACTWater sports center is the center of the ongoing activities and diversification of water sports in general carried out in the open. Planning Water sports center as a magnet and acceleration stimulus to the development of the realization of a facility that can provide added value to the region and the city of Palembang in particular Jakabaring and South Sumatra Province in general. Jakabaring retention lake has the potential to support activities that overlooks the water andthe edge of the lake. The concept of planning in the region Jakabaring Water Sports Center: First In climatological, landscape serves as a regulator of climate, as well as the dirty air filter media soil conservation and aesthetics of the area, the landscape is directed to maintain and preserve the environment, the third arrangement of the landscape adds value to the environment aesthetic, visual psychologically, socially and ecologically, the four landscape provides agood visual impression, comfortable, quiet and gives a sense of security on visitors, the five used to strengthen and establish the structure of the region, six landscape is used as a reinforcing element forming lanes and open spaces.Key words : Lake Retention, Water Sport Center, Climatological